Economics for the common good - Tirole, Jean, ....- (Princeton : Princeton University Press, 2016)
From the Nobel Prize-winning economist, a bold new agenda for the role of economics in society When Jean Tirole won the Nobel Prize in Economics, he suddenly found himself being stopped in the street by strangers and asked to comment on current events far from his own research. His transformation from academic economist to public intellectual prompted him to reflect more deeply on the role economists and their discipline play in society. The result is Economics for the Common Good, a passionate manifesto for a world in which economics can help us improve the shared lot of societies and humanity as a whole. To show how, Tirole shares his insights on a broad range of questions affecting our everyday lives and the future of our society, including global warming, unemployment, the post-2008 global financial order, the euro crisis, the digital revolution, innovation, and the proper balance between the free market and regulation. Compelling and accessible, Economics for the Common Good sets a new agenda for the role of economics in society.
Keywords: Economie